Advanced Practice Nursing Roles, Regulation, Education, and Practice: A Global Study - Kathy J. Wheeler; Minna Miller; Joyce Pulcini; Deborah Gray; Elissa Ladd; Mary Kay Rayens (Ubiquity Press, 2022)
Background and Objectives: Several subgroups of the International Council of Nurses Nurse Practitioner/Advanced Practice Nurse Network (ICN NP/APNN) have periodically analyzed APN (nurse practitioner and clinical nurse specialist) development around the world. The primary objective of this study was to describe the global status of APN practice regarding scope of practice, education, regulation, and practice climate. An additional objective was to look for gaps in these same areas of role development in order to recommend future initiatives. Methods: An online survey was developed by the research team, and included questions on APN practice roles, education, regulation/credentialing, and practice climate. The study was launched in August 2018 at the 10th Annual ICN NP/APNN Conference in Rotterdam, Netherlands. Links to the survey were provided there and via multiple platforms over the next year. Results: Survey results from 325 respondents, representing 26 countries, were analyzed through descriptive techniques. Although progress was reported, particularly in education, results indicated the APN profession around the world continues to struggle over titling, title protection, regulation development, credentialing, and barriers to practice. Conclusions and Practice/Policy Relevance: APNs have the potential to help the world reach the Sustainable Development Goal of universal health coverage. Several recommendations are provided to help ensure APNs achieve these goals.